حركة التفسير في الجزائر قبل ميلاد جمعية العلماء المسلمين الجزائريين: The interpretation movement in Algeria before the birth of the Algerian Muslim Scholars Association - Hayoune, Kamel; Norasid, Muhamad Alihanafiah; Abdullah, Mustaffa (Online Journal of Research in Islamic Studies, 2023)
The research deals with the study of the interpretation movement in one of the stages of its development in Algeria which extends from the late Ottoman era to the period before the birth of the Algerian Association of Muslim Scholars. The research aims to identify the interpreters of that stage and their books in interpretation, and it also aims to derive the result of the features of the interpretation in that stage and their causes. The research concluded by mentioning a several of Algerian interpreters who were preoccupied with interpretation in Algeria at that time, whether they were preoccupied with written or oral interpretation. Highlighting their written books in interpretation. The research also concluded that the state of the interpretation movement at that time was weak and traditional and plagued by stagnation because of several reasons and factors that arose from different sides.